Vertically Ordered Hematite Nanotube Array as an Ultrasensitive and Rapid Response Acetone Sensor - Kim, Do Hong; Shim, Young-Seok; Jeon, Jong-Myeong; Jeon, Hu Young; Park, Sung Soo; Kim, Young-Woon; Kim, Jin-Sang; Lee, Jong-Heun; Jang, Ho Won (American Chemical Society, 2014)
Vertically ordered nanotube array is a desirable configuration to improve gas sensing properties of the hematite which is the most abundant and cheapest metal oxide semiconductor on earth but has low and sluggish chemiresistive responses. We have synthesized a vertically aligned, highly ordered hematite nanotube array directly on a patterned SiO2/Si substrate and then it used as a gas sensor without additional processing. The nanotube array sensor shows unprecedentedly ultrahigh and selective responses to acetone with detection limits down to a few parts per billion and response time shorter than 3 s.
Keywords: GAS-SENSING PROPERTIES; HYDROTHERMAL SYNTHESIS; GROWTH-MECHANISM; ALPHA-FE2O3; TRANSPARENT; PERFORMANCE